Additive manufactured spherical resonator V‐band elliptical waveguide filter. Issue 2 (10th November 2021) - Liu, Wenbo; Huff, Gregory
Abstract: The design of an additively manufactured V‐band bandpass filter is proposed using spherical resonators with elliptical waveguides feeds. Compared with the traditional rectangular form, the curvilinear architecture seeks to mitigate corner radius effects in both the electromagnetic performance and additive manufacturing process. The filter and calibration components required for measurement are printed as single structures and then electroless silver plated using a closed‐loop bidirectional pump‐driven fluidic system. Simulated and measured results are provided.